The drug and criminal activity patterns of urban offenders: A Markov chain analysis - Pettiway, Leon E. (Journal of quantitative criminology, 1994)
In criminology, researchers have examined the role of lifestyle and activity patterns on criminal victimization. The vast majority of this research has focused on crime victims as a critical link in criminal victimization, but little attention has been given to the activity patterns of offenders or the connection between the various elements of the offenders' routine activities. This analysis presents a description of the activity patterns of 431 offenders who were heavily involved in crime during 1990–1991 in Philadelphia. A first-order Markov chain process best describes the manner in which offenders enter various activities. The preliminary analysis of these data not only provides additional support for the interrelationship between drug use and crime but also demonstrates that offenders participate in a wide array of activities.